Factors associated with vitamin D status of low-income, hospitalized psychiatric patients: results of a retrospective study - Bazzano AN; Littrell L; Lambert S; Roi C (Neuropsychiatric Disease and Treatment)
Alessandra N Bazzano,1 Lisa Littrell,1 Stephen Lambert,2 Cody Roi2 1Department of Global Community Health and Behavioral Sciences, Tulane University School of Public Health and Tropical Medicine, Tulane University, 2Department of Psychiatry, Louisiana State University Health Sciences Center, Louisiana State University, New Orleans, LA, USA Background: Recent evidence has indicated a potential role of vitamin D3 in a range of neuropsychiatric outcomes, as well as on cognitive function, but conflicting data have left that role uncertain. Understanding potential associations of vitamin D status with psychiatric illness will allow clinicians to better assess therapeutic options. Few studies have examined vitamin D status among a racially diverse group of psychiatric patients who have been hospitalized, and none has done so in the southern US where socioeconomic inequality is high.Methods: In this retrospective study, medical records from 113 patients hospitalized for psychiatric illness were retrieved and analyzed. Vitamin D status in this population was estimated, along with any patterns of association between deficiency and risk factors.Results: The vast majority of patients hospitalized for psychiatric illness in this biracial, low-income sample had either insufficient or deficient vitamin D levels. African-American patients had lower levels of vitamin D than Caucasian patients.Discussion: Our findings demonstrate that hospitalized psychiatric patients are at increased risk for vitamin D deficiency and in particular low-income, African-American populations. These results suggest that vitamin D should be assessed and therapy considered at the initiation of psychiatric hospitalizations. Keywords: vitamin D, psychiatric diagnosis, cognitive function, neuropsychological function